Collective Impact on Prevention: Let's Talk About Children Service Model and Decrease in Referrals to Child Protection Services - Niemelä, Mika; Kallunki, Hannu; Jokinen, Jaana; Räsänen, Sami; Ala-Aho, Birkitta; Hakko, Helinä; Ristikari, Tiina; Solantaus, Tytti (Frontiers in Psychiatry, 2019)
Families with parental mental health issues often have numerous problems needing multilevel measures to address them. The Let’s Talk about Children (LT) Model is a community-based approach aiming at an integrated service system to support family wellbeing and prevent child protection measures. Three municipalities in the Raahe District (RD) of Finland requested implementation of the LT Model. The paper describes the LT Model and the first results. Material and methods. The LT Model unites relevant stakeholders with families and their social networks aiming at the shared goal of supporting children’s everyday life at home, kindergarten, school and leisure environments. Parents, teachers and other caretakers are supported by LT intervention. An infrastructure for collaboration, decision making, monitoring, training and feedback is established, embracing health, social and educational services and other stakeholders. Referrals to child protection services were compared with national data before (2009–2013) and after implementation of the Model (2013–2016). The analyses were conducted using the joinpoint method. Results. There was a significant decrease in the underage population referred to child protection services in RD (AAPC = -6.9; p = 0.013) in 2013–2016, in contrast to an increase nationally (AAPC=1.9; p=0.020). Discussion. In the LT Model, prevention starts in children’s everyday life as the uniting, common goal for multiple stakeholders, and an integrated service structure is developed to support this. The first results are promising, showing a significant decrease in referrals to child protection services, although a longer follow-up and research across municipalities are needed.